2018
DOI: 10.3892/ol.2018.8551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of valproic acid on the susceptibility of human glioma stem cells for TMZ and ACNU

Abstract: To investigate the effect of valproic acid (VPA) on the susceptibility of glioma stem cells to temozolomide (TMZ) and nimustine (ACNU), the O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation and its expression of MGMT were examined. A total of 3 glioma cell populations were isolated from human glioma tissues, and immunocytochemistry was used to detect the expression of MGMT. VPA inhibition on the growth of the 3 glioma cell populations exposed to various concentrations of TMZ and ACNU was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…antitumor effects in glioma. For cytotoxic response, the combination of VPA and TMZ suppressed the survival rate and migration of glioma cells compared with that of the TMZ alone, which verified the sensitivity of VPA(28,31,33). More importantly, the combination induced apoptotic cell death, accompanied by enhanced…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…antitumor effects in glioma. For cytotoxic response, the combination of VPA and TMZ suppressed the survival rate and migration of glioma cells compared with that of the TMZ alone, which verified the sensitivity of VPA(28,31,33). More importantly, the combination induced apoptotic cell death, accompanied by enhanced…”
mentioning
confidence: 56%
“…All these findings manifested that VPA mainly exerted its biological activities via signalings and molecular targets mentioned above, providing evidence for pre-clinical experiments (Figure 2 and Table 1). (28). As for BCNU, detailed analysis of combination of VPA and BCNU revealed that the synergistic effect was mainly reflected in cell growth inhibition and cell-cycle arrest rather than an increased programmed cell death (23).…”
Section: Molecular Targetsmentioning
confidence: 99%
“…Zhiying Li et al reported survival rate in human glioma cell populations exposed to VPA + TMZ or ACNU was signi cantly decreased compared with that of the TMZ or ACNU alone groups. VPA not only enhanced the inhibitory effects of TMZ and ACNU but also induced tumor apoptosis [17]. However, there are researchers holding the converse opinion.…”
Section: Discussionmentioning
confidence: 99%
“…VPA is capable of inducing a predifferentiation state in GSCs ( 74 ) and can be combined with other antineoplastic compounds for synergistic effects, as reported for the antimitotic paclitaxel ( 82 ). However, VPA failed to sensitize GSCs to TMZ ( 74 ), although another study reported sensitization to both TMZ and nimustine (ACNU), especially in MGMT-expressing cells ( 83 ). VPA is able to modify the DNA methylomes of GSCs ( 74 ), leading to the activation of the Wnt/ β -catenin pathway which was related with growth inhibition, reduced migration and EMT impairment ( 84 ).…”
Section: Hdac Inhibitors As Therapeutic Agents In Gscsmentioning
confidence: 99%